Bioimpedance Spectroscopy Imprecisely Assesses Lean Body Mass in Pediatric Dialysis Patients. Issue 4 (October 2018) - Milani, Gregorio P.; Groothoff, Jaap W.; Vianello, Federica A.; Fossali, Emilio F.; Paglialonga, Fabio; Consolo, Sivia; Edefonti, Alberto; Consonni, Dario; van Harskamp, Dewi; van Goudoever, Johannes B.; Schierbeek, Henk; Agostoni, Carlo; et al.
ABSTRACT: Objectives: Alterations in body compositions are strongly associated with poor outcomes in end-stage renal disease patients. Hence, assessment of lean body mass is crucial for clinically monitoring these patients. The use of multifrequency bioimpedance spectroscopy measurements has also been advocated, but their usefulness in children is questioned. We investigated whether their application is appropriate for lean body mass measurement in pediatric patients receiving chronic dialysis. Methods: Lean body mass estimates as assessed by multifrequency bioimpedance spectroscopy and by deuterium dilution were obtained for 15 patients (mean age 10.9 ± 3.6 years). Results: Lean body mass (mean ± standard deviation) determined by bioimpedance was 24.2 ± 10.7 and 24.4 ± 10.3 kg by deuterium technique. Bland-Altman analysis showed a mean (±standard deviation) difference between the 2 methods of −0.25 ± 2.30 kg with 95% limits of agreement of −4.80 to 4.25 kg. In a multiple linear regression model, the hydration status was associated with measurement bias after adjusting for age, sex, weight, and body surface area. Conclusions: Our results show a high level of agreement between measurements by bioimpedance and deuterium technique, but the limits of agreement were wide. These findings do not support the use of bioimpedance to individually assess lean body mass in pediatric dialysis patients with and without overhydration.